The main features of the ukrainian grammar - Danylyuk, Nina; Masytska, Tetiana; O’Brien, Douglas; Rohach, Oksana (Волинський національний університет імені Лесі Українки, 2022)
The textbook provides a concise theoretical description of the morphology of the Ukrainian language, and the tasks and exercises that were created to enhance the acquisition of the material. The theoretical material is explained in English for the English speaking students who study Ukrainian as a foreign language to understand the key grammar terms and notions better. The textbook is based on the work: Notes on Ukrainian grammar for foreign students: learning materials of the Ukrainian grammar for the English speaking foreign students / Y. Horot, N. Danyliuk, L. Malimon, O. Rohach. Lutsk : LUEENU, 2014. 40 p. The textbook is for the learners of the preparatory departments and the students of higher educational institutions.
Основні риси граматики української мови
Keywords: 811.161.2’36(072)